Meltwater percolation, impermeable layer formation and runoff buffering on Devon Ice Cap, Canada. Issue 255 (8th February 2020) - Ashmore, David W.; Mair, Douglas W. F.; Burgess, David O.
Abstract: The retention of meltwater in the accumulation area of the Greenland ice sheet and other Arctic ice masses buffers their contribution to sea level change. However, sustained warming also results in impermeable ice layers or 'ice slabs' that seal the underlying pore space. Here, we use a 1-D, physically based, high-resolution model to simulate the surface mass balance (SMB), percolation, refreezing, ice layer formation and runoff from across the high-elevation area of Devon Ice Cap, Canada, from 2001 to 2016. We vary the thickness of the 'impermeable' ice layer at which underlying firn becomes inaccessible to meltwater. Thick near-surface ice layers are established by an initial deep percolation, the formation of decimetre ice layers and the infilling of interleaving pore space. The cumulative SMB increases by 48% by varying impermeable layer thickness between 0.01 and 5 m. Within this range we identify narrower range (0.25–1 m) that can simulate both the temporal variability in SMB and the observed near-surface density structure. Across this range, cumulative SMB variation is limited to 6% and 45–49% of mass retention takes place within the annually replenished snowpack. Our results indicate cooler summers after intense mid-2000s warming have led to a partial replenishment of pore space.